OPTIMIZATION ANTIBACTERIAL PRODUCTION TIME OF ACTINOMYCETES ISOLATES (TE 235 ISOLATES) AGAINS ANTIBACTERIAL ACTIVITY ON ESCHERICHIA COLI AND STAPHYLOCOCCUS AUREUS - Sutiara Prihatining Tyas; Alfian Syarifuddin; Ni Made Ayu Nila Septianingrum (Universitas Muhammadiyah Magelang, 2021)
The search for new Antibiotics is needed in the hospital because of the multi-resistance Antibiotics that result in an increase in deaths due to Antibiotic abuse in dealing with infectious diseases, so it is necessary to explore to get potential new antibiotics. Actinomycetes are microorganisms that can produce is antibiotics. Actinomycetes isolate (isolate TE 235) has been isolated from rizosphere soil of sugarcane root crops. This study aimed to determine the optimal time of TE 235 isolates in producing secondary metabolites in the form of antibiotics that can test bacteria Escherichia coli and Staphylococcus aureus and the growth profile of TE 235 isolates were reviewed based on the production of cell biomass. The activity test method used in this study is a suitable test method. The results showed that the liquid culture of Actinomycetes isolates (isolate TE 235) had an optimal time to produce secondary metabolites (Antibiotics) against Staphylococcus aureus bacteria after incubation for ten days with inhibition zone diameter of 6.67 ± 0.94 mm, whereas against Escherichia coli bacteria on the seventh day with a diameter of inhibitory zone of 10.00 ± 0.82 mm. The results of research on the growth of Actinomycetes bacteria isolate TE 235 based on the weight of cell biomass that underwent the stationary phase on the 9th day. The incubation time of the culture of Isolate TE 235 to obtain optimal approval of antibiotics after ten days of incubation in terms of antibiotic activity on Staphylococcus aureus and Escherichia coli and the growth phase of TE235 isolates as the stationary phase.